Efeitos da ampliaç\~ao dos direitos trabalhistas sobre a formalizaç\~ao, jornada de trabalho e salários das empregadas domésticas - Joana Sim\~oes Costa; Ana Luiza Neves de Holanda Barbosa; Guilherme Issamu Hirata (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This study analyzes the impact of the extensions in labor rights (foreseen in the Constitutional Amendment number 72 of April 2nd, 2013) over the legalization, working hours and wages of Brazilian domestic servants. We also aim to identify the effect of this new legislation in the probability of a woman becomes a housemaid, among other effects in labor status of domestic work. The methodology is based on the propensity score matching approach in order to construct the control group and in difference-in-difference estimation procedure to evaluate the casual effect. The analysis is carried out with microdata from Pnad/2011 through Pnad/2014. Our results suggest that this legislation increased the formal job positions, reduced the working hours and had no effect on wages of monthly domestic workers.
Keywords: J2; J4; J38; 330; domestic work; formal sector; working hours